Adoption Determinants of Adapted Climate Smart Agriculture Technologies Among Smallholder Farmers in Machakos, Makueni, and Kitui Counties of Kenya - Muriithi, Lydia N.; Onyari, Charles N.; Mogaka, Hezron R.; Gichimu, Bernard M.; Gatumo, Geoffrey N.; Kwena, Kizito (My University, 2021)
The study examined the adoption determinants of adapted climate smart agriculture (CSA) technologies among smallholder farmers. A multi-stage sampling procedure was used to select a total sample of 384 households. Percentages and regression were employed in data analysis. The results revealed that 47.4% adapted to climate change using integrated farming system, intercropping, crop rotation and agroforestry. Sex (0.9%), education level (9.2%) significantly influenced adoption of the adaptation strategies. Moreover, information sources such as mobile phones (0.9%), and neighbors/friends (0.2%) negatively affected the adaptation strategies. Future policy should aim at creating more awareness through different information sources and provide local extension services.
Keywords: Adaptation; smallholder farmers